(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract How to fill in the partograph is very important to know the signs of early complications in labor. The purpose of this study was to determine the relationship between knowledge of the partograph by filling in the partograph on midwifery students Indragiri level III at the Indragiri Midwifery Academy. Analytical design with cross sectional approach with the sampling technique was total sampling. The results showed that most or 10 of the 56 respondents (100%) had good knowledge and filled out the partograph completely, while 0 out of 56 respondents (0%) had less knowledge and filled out the partograph completely. Most or 42 of the 56 respondents (91.3%) have good knowledge and fill in partographs incompletely, while a small proportion or 4 of the 56 respondents (8.7%) have less knowledge by filling in an incomplete partograph the conclusion of this study is There was no significant relationship between knowledge by filling in the partograph of the student AKBID Indragiri Rengat with a P value> 0.05.